ANALISIS PENGARUH SERVICE QUALITY, WORK PERFORMANCE, COOPERATIVE MOTIVATION DAN COOPERATIVE KNOWLEDGE TERHADAP COOPERATIVE SUCCESS DIMEDIASI MEMBER PARTICIPATION KOPERASI PEGAWAI REPUBLIK INDONESIA (KPRI) “LESTARI” KECAMATAN TIKUNG (METODE (SEM) STRUCTURA - Nafisa, Zahrotun; Muhtarom, Abid; Nurcholidah, Lilik (Jurnal Penelitian Manajemen Terapan (PENATARAN), 2024)
Human resources are essentially one of the key components that play a vital role in accomplishing company goals, one of which is cooperatives. Every cooperative if you want to develop properly. Therefore, cooperative knowledge possessed by members of the cooperative will determine the success of the cooperative. Researchers used a type of quantitative approach, a sample of 175 based on non-probability sampling techniques with saturated samples, with SEM analysis using the Smart application. PLS version 3.0. By testing the Outer Model, Inner Model Test, Mediation Test and Hypothesis Test. The results of the Validity test stated that the Loading Factor number of more than 0.7 and the AVE number values exceeding 0.5 were deemed valid in the Reliability test, specifically for the Composite Reliability value and Cronbach's Alpha above 0.7 were declared strong. The conclusion obtained is that the variables Service Quality (X1), Work Performance (X2), Cooperative Motivation (X3), Cooperative Knowledge (X4) have a positive and significant effect on Cooperative Success (Y) mediated by member participations (Z). In the mediation test, the variables Service Quality (X1), Work Performance (X2), Cooperative Motivation (X3), Cooperative Knowledge (X4) on Cooperative Success (Y) mediated by member participations (Z) are said to be partial mediation. Keywords: Cooperative Knowledge, Cooperative Motivation, Cooperative Success, Member Participations, Service Quality, SEM PLS, and Work Performance.